2017
DOI: 10.1080/13561820.2017.1341867
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for interprofessional facilitators and clinical supervisors that may enhance the emotional intelligence of therapy students

Abstract: Emotional intelligence (EI) is a critical skill for occupational therapy, physiotherapy, and speech pathology students (therapy students). This article reports the findings from an analysis of interviews with therapy students (n = 24) to determine the aspects of clinical placements that therapy students perceived as influencing the changes in EI scores. This article reports the findings of the qualitative phase of a longitudinal, retrospective mixed methods design. Interviewees were selected using purposive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Students were on placements for a mean of 117 days of the 16-month (approximately 480 days) period; thus despite the control group, we cannot conclusively state that the changes in emotional intelligence scores of the occupational therapy students were a direct result of their placements because they were also involved in further teaching at university, paid or volunteer employment, as well as personal life events over the same period. Further qualitative research by (Gribble et al., 2017c) on the development of emotional intelligence in students during practice placement found majority of emotional intelligence changes (95%) were reported to be a direct result of their practice placements, with only 5% perceiving that the emotional intelligence change was due to personal factors external to placements. This study interviewed occupational therapy, physiotherapy and speech pathology students about how practice placements influenced changes in their emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students were on placements for a mean of 117 days of the 16-month (approximately 480 days) period; thus despite the control group, we cannot conclusively state that the changes in emotional intelligence scores of the occupational therapy students were a direct result of their placements because they were also involved in further teaching at university, paid or volunteer employment, as well as personal life events over the same period. Further qualitative research by (Gribble et al., 2017c) on the development of emotional intelligence in students during practice placement found majority of emotional intelligence changes (95%) were reported to be a direct result of their practice placements, with only 5% perceiving that the emotional intelligence change was due to personal factors external to placements. This study interviewed occupational therapy, physiotherapy and speech pathology students about how practice placements influenced changes in their emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…This article reports the results from only the occupational therapy students. Phase two interviewed 24 of the same students to investigate if, and how, practice education influenced changes in emotional intelligence scores (Gribble et al., 2017c).…”
Section: Methodsmentioning
confidence: 99%
“…Grenier [35] reported that clinical supervisors who demonstrate poor communication skills, disengagement, high levels of control, being closed-minded or supervised with intimidation could negatively impact a student’s performance. Gribble et al [27] also reported that clinical supervisors could have a negative impact on the EI competencies of therapy students.…”
Section: Discussionmentioning
confidence: 99%
“…Students who experience difficulty during placements have been reported to demand additional time from supervisors [39], thus students with lower EI scores may also require additional support, although more research is required ot confirm this possibility. Supervisors need to be aware that a poor supervisory environment might impact a student’s EI skills [27]. For example, an intimidating or disengaged supervisor might diminish a student’s assertiveness and self-expression, which consequently impacts the student’s performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation